Pengaruh Gaya Hidup, Online Customer Review Dan E-Wom Terhadap Keputusan Pengguna Aplikasi Ovo Di Solo Raya - Cindy Dayinta Puspitasari; Ari Susanti (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the analysis of the influence of lifestyle, OCR and E-WOM on the decisions of OVO application users. This research method is associative research where the research method is a quantitative approach. This study uses a questionnaire to share basic data. In this study, the population is all the people of Solo Raya and the research sample is 100 respondents, and the sampling method uses Purposive Sampling and uses the roscoe formula, the analytical method is assisted by SPSS version 25. The data analysis method uses Instrument Tests, Classical Assumptions tests, and Multiple Regression Tests. secondary data obtained from books that reveal user decisions, the internet and previous research journals. The results of this study conclude that simultaneously (F test) shows if there is a significant effect between lifestyle, OCR, and E-WOM on user decisions..